CAER: Co-creating a Collaborative Documentary about the Lives and Rights of Trans Latinx People Working in the Sex Industry in Queens, NYC - Mai, Nicola; Winslet, Liaam (Anti-Trafficking Review, 2022)
This short article describes the co-creative production process of the film CAER—a collaboration between a researcher/film director and the Colectivo Intercultural TRANSgrediendo: a collective of migrant Latinx trans people in Queens, New York. It shows how the filmmaking process was guided by the concerns of the community, whose members co-wrote the script and took an active part in editing the raw material. The collaboration was born out of the shared belief that communities impacted by policies need to own the terms of their representation.